Expressão dos micro-RNAs-19a, -24, -25, -29a e -483 no soro de pacientes portadores de adenocarcinoma de pâncreas com diabetes mellitus - Peixoto, Renata D'Alpino (2020)
Background: Pancreatic ductal adenocarcinoma (PDA) is one of the most lethal types of cancer and its clinical manifestations usually occur at an advanced stage of the disease, when the chances of surgery and cure are low. To date, there is no indication of screening for PDA in the asymptomatic general population, but it is known that, although long-term type 2 diabetes (T2D) is a modest risk factor for PDA, new-onset diabetes (DM) can be considered a possible marker of this neoplasm, showing a bidirectional relationship between PDA and DM. Aims: The aim of the present study was to evaluate the expression of micro-RNAs (miRs) -19a, -24, -25, -29a and -483, previously identified as potential PDA biomarkers in individuals with new-onset DM, in the serum of individuals with PDA and new-onset DM compared to individuals with long-term DM2 and to individuals without these two clinical conditions. Methods: 44 individuals with PDA (21 with new-onset DM, 9 with long-term DM, 1 with DM of unknown duration, and 13 without DM), 35 individuals with long-term T2D and 35 Control individuals without these clinical conditions were included. Peripheral blood was collected to quantify the miRs by quantitative polymerase chain reaction after reverse transcription (RT-qPCR). Results: MiRs-24 and -29a were more expressed in the serum of individuals with PDA compared to individuals with T2D and to Control individuals. MiRs-19a and -25 were more expressed in the serum of Control individuals compared to individuals with PDA and with T2D. There were no differences in miR-483 expression among the three groups. The comparison between individuals with PDA and new-onset DM and individuals with T2D showed a greater expression of miRs-24 and -29a in the first group, with loss of statistical significance after adjustment for confounding variables. The analysis of the ROC curves after adjusting for the body mass index showed areas under the curves with values greater than 0.853 for the five miRs. Conclusions: MiRs-24 and -29a were more expressed in the serum of individuals with PDA and new-onset DM compared to individuals with T2D; they were also more expressed in the total population of individuals with PDA in comparison to individuals with T2D and to Control individuals. The results of the ROC curves suggest that the five evaluated miRs could be used to discriminate new-onset DM associated with PDA from DM2.